(Un)principled principals, (un)principled agents: The differential effects of managerial civil service reforms on corruption in developing and OECD countries. Issue 4 (26th August 2020) - Schuster, Christian; Meyer‐Sahling, Jan‐Hinrik; Mikkelsen, Kim Sass
Abstract: Do management practices have similar anticorruption effects in OECD and developing countries? Despite prominent cautions against "New Zealand" reforms which enhance managerial discretion in developing countries, scholars have not assessed this question statistically. Our article addresses this gap through a conjoint experiment with 6, 500 public servants in three developing countries and one OECD country. Our experiment assesses Weberian relative to managerial approaches to recruitment, job stability, and pay. We argue that in developing countries with institutionalized corruption and weak rule of law—yet not OECD countries without such features—"unprincipled" principals use managerial discretion over hiring, firing, and pay to favor "unprincipled" bureaucratic agents who engage in corruption. Our results support this argument: managerial practices are associated with greater bureaucratic corruption in our surveyed developing countries, yet have little effect in our OECD country. Alleged "best practices" in public management in OECD countries may thus be "worst practices" in developing countries.